Iodine nutrition in pregnancy - Delshad, Hossein (Annals of Thyroid; Vol 3 (September 2018): Annals of Thyroid, 2018)
Due to its role as a component of thyroid hormones, iodine is considered an essential nutrient. These hormones cross the placenta early in pregnancy and are essential for brain development and maturation of the fetus during early pregnancy. The critical period for this dependency extends from intrauterine life to 3 years of age. Iodine requirements increase dramatically during pregnancy and lactation. Pregnant and breastfeeding women need extra iodine to help ensure their iodine needs are met. Inadequate iodine intake during these period leads to insufficient production of thyroid hormones. Sever iodine deficiency has negative effects on normal physical growth and mental development of children, whereas the consequences of mild to moderate deficiency are less clear. The elimination of iodine deficiency is relatively simple and feasible through iodine supplementation. Among the many methods of prevention, iodized oil and salt iodization programs have been implemented in many countries. Since 1999, the number of countries with effective salt iodization as a safe, cost-effective, and sustainable strategy to ensure sufficient intake of iodine has increased to the point that today over 80% of the world has access to adequately iodized salt. Although iodized salt is commonly the main source of iodine for general populations, iodine supplements are recommended by different medical societies during pregnancy and lactation.